2014
DOI: 10.3329/bjvm.v12i1.20464
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical Mastitis in Lactating Cows and Efficacy of Intramammary Infusion Therapy

Abstract: The aim of the study was to estimate the prevalence of subclinical mastitis (SCM) in lactating cows of Mymensingh and Lakshmipur sadar upazilas and to evaluate the efficacy of intramammary infusion in subclinical mastitis affected cows. A cross-sectional study was carried out on 78 smallholder dairy farms using a pretested questionnaire to collect data from June 2011 to May 2012. Milk samples from 139 lactating cows were screened for SCM by California Mastitis Test. A total of 72 cows was found positive for SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(21 reference statements)
3
8
1
Order By: Relevance
“…The Right hind (RH) quarter was the second followed by Left hind (LH) and Left front (LF) quarter. The quarter wise prevalence of the present result disagree with the report of [51] who reported 28.1% in Left Front (LF), 33.1% in Left Hind (LH), 24.5% in Right Front (RF), and 17.3% in Right Hind (RH) quarters which was higher in prevalence in Left Front (LF) and Left Hind (LH) quarters. Higher prevalence of subclinical mastitis in Right front (RF) and Right hind (RH) compared to the other two quarter found in the present study was most probably due to the ease of grasping the right front quarters first while milking and the higher production capacity of hind quarters [11] and the chance of getting environmental and fecal contamination also in the case of hind quarters [33].…”
Section: Discussioncontrasting
confidence: 99%
“…The Right hind (RH) quarter was the second followed by Left hind (LH) and Left front (LF) quarter. The quarter wise prevalence of the present result disagree with the report of [51] who reported 28.1% in Left Front (LF), 33.1% in Left Hind (LH), 24.5% in Right Front (RF), and 17.3% in Right Hind (RH) quarters which was higher in prevalence in Left Front (LF) and Left Hind (LH) quarters. Higher prevalence of subclinical mastitis in Right front (RF) and Right hind (RH) compared to the other two quarter found in the present study was most probably due to the ease of grasping the right front quarters first while milking and the higher production capacity of hind quarters [11] and the chance of getting environmental and fecal contamination also in the case of hind quarters [33].…”
Section: Discussioncontrasting
confidence: 99%
“…The current findings corroborate with those reported in recent studies and in the same country (51.8%) [ 21 ] using electrical conductivity and in Tanzania (51.6%) [ 22 , 23 ], in Ethiopia, all have used CMT to screen for SCM at cow level. It was also similar to those reported from other countries: 49.5%, 51.8%, and 52.4% in South Wales in Australia [ 24 ], in Bangladesh [ 25 ], and in Uruguay [ 26 ], respectively, all using CMT. However, this reported that SCM prevalence was lower than those reported in recent studies in East Africa; 86.2%, 64% and 59.2% in Uganda [ 27 ], in Kenya [ 28 ], and [ 23 ] in Ethiopia, respectively, and elsewhere, 88.6%, by [ 29 ] in Vietnam all have used CMT to screen for SCM at cow level.…”
Section: Discussionsupporting
confidence: 89%
“…However, Sarker et al [23] and Sumon et al [17] found only 20.2% and 25% prevalence of SCM in dairy cows, respectively. A medium ranged prevalence of SCM (50.4% and 58%, respectively) was reported by Tripura et al [24] and Mpatswenumugabo et al [25]. This variation might be due to differences in management practices of the cows and geographical location.…”
Section: Resultsmentioning
confidence: 77%